전통주 국내외 산업현황 및 세계화 가능성 조사 - 이동필 (한국농촌경제연구원, 2009)
The purpose of this study is to identify current situations and problems of the Korea traditional liquor industry, and to figure promotional strategies for the industry and globalize Korea tradition liquor out. The development of the Korea traditional liquor industry operates to save foreign currency through substitution with Korea liquor, helps the stability of the food supply and demand, and increases farm's income by using domestic agricultural products. Moreover, the Korea liquor industry helps enhancing people's health with traditional food made of domestic raw materials such as rice, fruit, and medicinal herb etc. According to the research, the following policies are recommended to meet developments and globalization in the Korea traditional liquor industry: (1) deregulate and reform the policy in the standardization and manufacturing methods after clearing the definition of the Korea traditional liquor, (2) diversify manufacturing methods and allow utilization of various raw materials, (3) reform the quality control and indication system for the Korea traditional liquor industry, (4) establish sustainable raw material supply system and facilitate utilization of demestic products, (5) enforce for promotion of sales and advertisement, (6) revise tax system and provide incentive measures for small farmer's liquor and traditional folk liquor businesses which are using the utilization of various raw materials.